2004
DOI: 10.1056/nejmoa031681
|View full text |Cite
|
Sign up to set email alerts
|

Use of B-Type Natriuretic Peptide in the Evaluation and Management of Acute Dyspnea

Abstract: Used in conjunction with other clinical information, rapid measurement of B-type natriuretic peptide in the emergency department improved the evaluation and treatment of patients with acute dyspnea and thereby reduced the time to discharge and the total cost of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
419
2
30

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 897 publications
(461 citation statements)
references
References 27 publications
10
419
2
30
Order By: Relevance
“…A commonly used biochemical marker for severity of HF is pro-BNP, which has been shown to correlate with the severity of HF [24,25]. In the present study, the VO 2 peak/THV ratio was shown to correlate with pro-BNP, indicating that the ratio can potentially serve as a measure for severity of HF.…”
Section: Discussionsupporting
confidence: 61%
“…A commonly used biochemical marker for severity of HF is pro-BNP, which has been shown to correlate with the severity of HF [24,25]. In the present study, the VO 2 peak/THV ratio was shown to correlate with pro-BNP, indicating that the ratio can potentially serve as a measure for severity of HF.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, NT-proBNP measurements might prove valuable for enrichment of diabetic patient populations in future intervention trials, including studies of cardioprotective treatment aiming to demonstrate that specific modification of this marker will translate into improved outcome, as suggested in patients with heart failure [31] and emergency patients with dyspnoea [32]. In addition, determination of plasma NT-proBNP concentration will enable the identification of type 1 diabetic patients with nephropathy with a relatively low 10-year mortality rate, a rate approaching the risk in diabetic patients with persistent normoalbuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating levels of the cardiac natriuretic peptides, particularly brain natriuretic peptide (BNP) and the 1-76 amino-acid N-terminal pro-BNP (NT-proBNP), have been identified as robust biochemical markers of heart failure in patients presenting with acute shortness of breath, [1][2][3][4] as prognostic indices for mortality and the development of heart failure following acute myocardial infarction, 5,6 and as potentially useful guides to the intensity of pharmacotherapy in patients with chronic heart failure. 7 Natriuretic peptide levels have been reported also to be higher in patients with hypertension, especially those with left ventricular hypertrophy or dysfunction, than in normotensive subjects.…”
Section: Introductionmentioning
confidence: 99%